- 1-800-665-6601
- [email protected]

Solution: Given is the equation 2x/(x + 1) + 1 = 1/(x+1).

Here the left had side has the equation 2x/(x + 1) + 1.

Take the common denominator that will be (x + 1)

2 x /(x + 1) + (x + 1) / (x + 1) = (2 x + x + 1)/(x+1) = (3 x + 1)/ (x + 1).

This gives: (3 x + 1)/ (x + 1)

The denominator on both sides is (x + 1) equating the numerators.

This gives: 3 x + 1 = 7.

Subtract 1 on both sides.

This gives 3 x = 6.

Divide both sides of the equation by 3.

Solution: Given is the equation 4x/(x + 12) = 1.

Multiply both sides of the equation by x+12.

This give 4x = x+ 12.

Subtracting both sides of the equation by x. 3x = 12.

Divide both sides of the equation by 3.